2018
DOI: 10.4084/mjhid.2018.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of the SOD2 polymorphism (Val6Ala) and SOD activity with vaso-occlusive crisis and acute splenic sequestration in children with sickle cell anemia

Abstract: The SOD2 polymorphism Val16Ala T→C influences the antioxidative response. This study investigated the association of the SOD2 polymorphism and superoxide dismutase (SOD) activity with the vaso-occlusive crisis (VOC) and acute splenic sequestration (ASS) in children with sickle cell anemia (SCA). One hundred ninety-five children with SCA aged 1–9 years old were analyzed. The TC and CC genotypes were associated with lower SOD activity compared with the TT genotype (p=0.0321; p=0.0253, respectively). Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
9
2
Order By: Relevance
“…The genotypic and allelic frequencies of SOD2 Val16Ala polymorphism in our cohort of Egyptian SCD patients were close to that reported in Brazilian patients. 14 The polymorphic (C) allele frequency in our SCD patients was 0.44, while it was 0.35 in Turkish patients 20 and 0.52 in Brazilian patients. 14 The Turkish and Brazilian studies and ours showed no statistical difference in SOD2 allelic and genotypic frequencies between SCD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The genotypic and allelic frequencies of SOD2 Val16Ala polymorphism in our cohort of Egyptian SCD patients were close to that reported in Brazilian patients. 14 The polymorphic (C) allele frequency in our SCD patients was 0.44, while it was 0.35 in Turkish patients 20 and 0.52 in Brazilian patients. 14 The Turkish and Brazilian studies and ours showed no statistical difference in SOD2 allelic and genotypic frequencies between SCD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 59%
“…As previously described, the assay was designed using Taq-Man SNP Genotyping Assays (Assay ID: C_8709053_10, Applied Biosystems, Thermofisher, Foster City, CA, USA). 14 20% of the samples were randomly chosen concerning case/control status and reanalyzed to validate our results. The results were interpreted by different observers and were found to be 100% concordant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOD2 Val-16-Ala polymorphism was studied many times in numerous diseases with very conflicting results. In SCA, it was recently associated with a lower MnSOD activity and a higher prevalence of acute splenic sequestration [ 30 ]. Quite interestingly, we also found a tendency for lower MnSOD activities for the eight children who recently developed an acute splenic sequestration but without any relation with the SOD2 Val-16-Ala polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 29 ], a composite HbF QTL score ranging from 0 to 6 and corresponding to the number of HbF-promoting alleles was calculated with these data. Finally, three SNPs previously described as affecting the activity of their respective oxidative stress enzyme were genotyped: rs4880 for the SOD2 gene [ 30 ], rs207454 for the XO gene [ 31 ], and rs2333227 for the MPO gene [ 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%